Validation of elevated levels of interleukin-8 in the cerebrospinal fluid, and discovery of new biomarkers in patients with GBS and CIDP using a proximity extension assay - Kmezic, Ivan; Gustafsson, Rasmus; Fink, Katharina; Svenningsson, Anders; Samuelsson, Kristin; Ingre, Caroline; Olsson, Tomas; Hansson, Magnus; Kockum, Ingrid; Adzemovic, Milena Z.; Press, Rayomand (Frontiers in Immunology, 2023)
Biomarkers for diagnosis of inflammatory neuropathies, assessment of prognosis, and treatment response are lacking.CSF and EDTA plasma from patients with Guillain-Barré syndrome (GBS), chronic inflammatory demyelinating polyneuropathy (CIDP), healthy controls (HC) and disease controls were analyzed with Olink multiplex proximity extension assay (PEA) from two independent cohorts. Levels of interleukin-8 (IL8) were further analyzed with ELISA in patients with GBS, CIDP, paraproteinemia-related demyelinating polyneuropathy (PDN), multifocal motor neuropathy (MMN), HC and disease controls. ROC analysis was performed.Cause and Treatment (INCAT) score.In CSF, multiplex PEA analysis revealed up-regulation of IL8 in GBS compared to CIDP and HC respectively, and CIDP compared to HC. In addition, levels of IL2RA were upregulated in GBS compared to both HC and CIDP, SELE in GBS compared to HC, and ITGAM, IL6, and NRP1 in GBS compared to CIDP. In plasma, levels of MMP3, THBD and ITGAM were upregulated in CIDP compared to HC. Validation of multiplex IL8 results using ELISA, revealed increased levels of IL8 in CSF in patients with GBS and CIDP versus HC and noninflammatory polyneuropathies (NIP) respectively, as well as in PDN versus NIP and HC. Levels of IL8 in CSF correlated with impairment in the acute phase of GBS as well as outcome at 6-months follow up.IL8 in CSF is validated as a diagnostic biomarker in GBS and CIDP, and a prognostic biomarker in GBS. Multiplex PEA hereby identifies several potential biomarkers in GBS and CIDP.